Safety and efficacy of novel malaria vaccine regimens of RTS, S/AS01B alone, or with concomitant ChAd63-MVA-vectored vaccines expressing ME-TRAP. (December 2018) - Rampling, Tommy; Ewer, Katie; Bowyer, Georgina; Edwards, Nick; Wright, Danny; Sridhar, Saranya; Payne, Ruth; Powlson, Jonathan; Bliss, Carly; Venkatraman, Navin; Poulton, Ian; Graaf, Hans; et al.
Abstract We assessed a combination multi-stage malaria vaccine schedule in which RTS, S/AS01B was given concomitantly with viral vectors expressing multiple-epitope thrombospondin-related adhesion protein (ME-TRAP) in a 0-month, 1-month, and 2-month schedule. RTS, S/AS01B was given as either three full doses or with a fractional (1/5th) third dose. Efficacy was assessed by controlled human malaria infection (CHMI). Safety and immunogenicity of the vaccine regimen was also assessed. Forty-one malaria-naive adults received RTS, S/AS01B at 0, 4 and 8 weeks, either alone (Groups 1 and 2) or with ChAd63 ME-TRAP at week 0, and modified vaccinia Ankara (MVA) ME-TRAP at weeks 4 and 8 (Groups 3 and 4). Groups 2 and 4 received a fractional (1/5th) dose of RTS, S/AS01B at week 8. CHMI was delivered by mosquito bite 11 weeks after first vaccination. Vaccine efficacy was 6/8 (75%), 8/9 (88.9%), 6/10 (60%), and 5/9 (55.6%) of subjects in Groups 1, 2, 3, and 4, respectively. Immunological analysis indicated significant reductions in anti-circumsporozoite protein antibodies and TRAP-specific T cells at CHMI in the combination vaccine groups. This reduced immunogenicity was only observed after concomitant administration of the third dose of RTS, S/AS01B with the second dose of MVA ME-TRAP. The second dose of the MVA vector with a four-week interval caused significantly higher anti-vector immunity than the first and may have been the cause of immunological interference. Co-administration of ChAd63/MVA ME-TRAP with RTS, S/AS01B led to reduced immunogenicity and efficacy, indicating the need for evaluation of alternative schedules or immunization sites in attempts to generate optimal efficacy. Malaria: Efficacy of a multi-stage vaccination for Malaria A number of Malaria vaccine candidates are currently under consideration. Targeting of multiple stages in the life cycle ofPlasmodium falci p arum, the causative agent of Malaria may increase vaccine efficacy. Clinical studies of such combinatorial vaccine approaches are required. Here Adrian Hill and colleagues at the University of Oxford report on their phase I/IIa study where they examine the effects of multiple combinational vaccine approaches that target the multiple stages of the parasite life cycle in a controlled human malaria infection model, assessing the efficacy and safety of these approaches in human volunteers prior to infection. Reduced immune responses and protection from Malaria infection was observed with co-administration of ME-TRAP containing vaccines. This study highlights a need to fully evaluate vaccination approaches to established more efficacious immunization protocols for Malaria and the potential of multi-stage approaches.